2016
DOI: 10.3892/or.2016.4824
|View full text |Cite|
|
Sign up to set email alerts
|

MicroRNA-18b inhibits the growth of malignant melanoma via inhibition of HIF-1α-mediated glycolysis

Abstract: Abstract. MicroRNAs (miRs) have been demonstrated to play critical roles in the development and progression of malignant melanoma (MM). However, the exact role and underlying mechanism of miR-18b in MM growth remains unclear. In the present study, real-time PCR data indicated that miR-18b was significantly downregulated in MM tissues compared to their matched adjacent non-tumor tissues. Low miR-18b expression was significantly associated with the tumor thickness and stage, although no significant association w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 29 publications
1
20
0
1
Order By: Relevance
“…miR-18b expression is dysregulated in several types of human cancer. miR-18b is downregulated in melanoma tissues and cell lines, and decreased levels are also significantly associated with tumor thickness and stage (15). Additionally, miR-18b has been reported to be upregulated in colorectal cancer.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…miR-18b expression is dysregulated in several types of human cancer. miR-18b is downregulated in melanoma tissues and cell lines, and decreased levels are also significantly associated with tumor thickness and stage (15). Additionally, miR-18b has been reported to be upregulated in colorectal cancer.…”
Section: Discussionmentioning
confidence: 98%
“…Numerous studies have reported that miR-18b contributes to the malignant phenotype of cancers. Upregulation of miR-18b has been demonstrated to inhibit melanoma cell proliferation, migration, invasion, glycolysis and epithelial-to-mesenchymal transition in vitro, increase apoptosis in vitro and reduce tumor growth in vivo (15,28). miR-18b has been validated as an oncogene in colorectal cancer via participation in the regulation of cell cycle, proliferation and migration (16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, accumulating evidence has revealed that miRNAs function as tumor suppressors or promoters. In our previous study, we confirmed that miR-33a, miR-199a, miR-18b, and miR-138 function as tumor suppressors by targeting oncogenes in melanoma Research Paper [9][10][11][12]. We interestingly found that miR-494 was abnormal low expression in melanoma cell than that in melanocytes via analyzing gene microarray results from Gene Expression Omnibus (GEO) datasets, suggesting miR-494 may play important role in melanoma progress.…”
Section: Introductionmentioning
confidence: 60%
“…They provided evidence of microRNA-18b binding to the HIF-1α 3′-UTR, while ectopic expression of this microRNA inhibited glycolysis and cell proliferation. [76, 77]. Hence HIF-1α coordinates multiple steps in glycolysis from glucose transport to lactate efflux allowing cancer cells satisfy their “addiction to glucose”.…”
Section: Hif Upregulation In Cancer: Consequencesmentioning
confidence: 99%